2009
DOI: 10.1080/01421590902744878
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence first year medical students’ choice of student selected component

Abstract: Background: Undergraduate medical training should ensure students have choice and autonomy in the learning process, including the student selected components (SSCs) which should comprise up to about a third of the curriculum. Students' choices of SSC will influence the knowledge, skills and attitudes they acquire. Aim: To investigate how motivations and personality in first year medical students influence their choice of SSCs. Method: A questionnaire regarding motivations for SSC choice and the NEO-FFI persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…These data are partially in agreement with previously published data regarding the relationship between motivation and SSC selection in first year undergraduate students. In the study by Richardson (2009), students motivated by future achievements, thematically comparable to the 'career strategy' category in this study, were more likely to select SSCs which promoted what they term 'generic skills'this category included research project experience, as well as teaching and learning in medicine. This study raises questions concerning the nature of the strong association between research and self-directed learning and a prominent career-focused motivation profile.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These data are partially in agreement with previously published data regarding the relationship between motivation and SSC selection in first year undergraduate students. In the study by Richardson (2009), students motivated by future achievements, thematically comparable to the 'career strategy' category in this study, were more likely to select SSCs which promoted what they term 'generic skills'this category included research project experience, as well as teaching and learning in medicine. This study raises questions concerning the nature of the strong association between research and self-directed learning and a prominent career-focused motivation profile.…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, we need to know whether students are strategic in their selections or whether they are guided by short-term and less challenging criteria (Babad & Tayeb 2008). A recent questionnaire-based analysis of motivational factors contributing to selection of SSC modules by first year undergraduates at a London medical school demonstrated that SSC selections were stratified across the following identified motivational factors: future achievements, prior information, internal motivation, personal recommendation, convenience and certainty (Richardson 2009). However, it is recognised that students also select different SSCs across the curriculum depending on evolving skills, knowledge, motivations, as well as awareness of future career possibilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plusieurs auteurs se sont déjà focalisés sur les choix et la motivation des étudiants en formation dans le domaine de la santé (e.g. Beaulieu, Haggerty, Bouharaoui, & Goulet, 2010 ;Choucair, Nemr, Sleilaty, & Abboud, 2007 ;Richardson, 2009). Cependant, la majorité de ces études concernaient d'autres choix que le choix initial de s'engager en sciences de la santé.…”
Section: Littérature Relative Aux Choix D'études Et De Métiersunclassified
“…The staff and students are hardly exposed to the concept and modern technologies which can be utilised for a research purpose (Kumar et al, 2009;Packiri, 2017). The postgraduate stu-dents in India undergo both clinical training and research (Richardson, 2009). However undergraduate curriculum does not include the concept of clinical trial.…”
Section: Introductionmentioning
confidence: 99%